The Concept of Impeachment in The Indonesia's Constitutional System From The Perspective of Fiqh Siyasah - Marwing, Anita; Asni, Asni; Astuti, Widia (al-'adalah, 2022)
This study discusses the Siyasah Fiqh Review of the concept of Impeachment in the Indonesian State Administration. The aim is to find out and understand the mechanism for impeachment/dismissal of the President or Vice President in Indonesia's constitutional system as stipulated in Articles 7 a and 7 b of the 1945 Constitution and the fiqh siyasa perspective on these rules. This research belongs to normative legal research that uses normative, juridical, and historical approaches. Data were collected using literary techniques, then analyzed descriptively and qualitatively. The results of this study indicate that the practice of impeaching the President in the past occurred more often due to political issues, namely the disputes between the legislature and the executive regarding the issue that the President had violated the law. In the past two impeachment proceedings, there has been no precise regulation regarding the impeachment mechanism of the President in the country's Constitution. After the amendment, the issue of impeachment was adopted in Articles 7A and 7B of the 1945 Constitution. Article 7A limits the grounds for impeachment, while Article 7B complicates impeachment by the presence of a judicial institution. From the perspective of Fiqh,siyasa, the head of State's impeachment can be carried out if it meets the criteria and reasons that Syara has determined'